2023
DOI: 10.1002/dvg.23529
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal plasticity in kidney fibrosis

Abstract: SummaryEpithelial–mesenchymal transition (EMT) is an important biological process contributing to kidney fibrosis and chronic kidney disease. This process is characterized by decreased epithelial phenotypes/markers and increased mesenchymal phenotypes/markers. Tubular epithelial cells (TECs) are commonly susceptible to EMT by various stimuli, for example, transforming growth factor‐β (TGF‐β), cellular communication network factor 2, angiotensin‐II, fibroblast growth factor‐2, oncostatin M, matrix metalloprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…The profibrotic response in renal tubular epithelial cells induced by TGF-β1 has been extensively utilized as an in vitro model to study renal tubulointerstitial fibrosis [ [34] , [35] , [36] , [37] ]. The EMT triggered by TGF-β1 closely mimics a crucial pathological event in the progression of renal tubulointerstitial fibrosis [ 38 ]. In this work, we constructed the in vitro model of renal tubulointerstitial fibrosis by stimulating human renal proximal tubular epithelial cells HK-2 with TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…The profibrotic response in renal tubular epithelial cells induced by TGF-β1 has been extensively utilized as an in vitro model to study renal tubulointerstitial fibrosis [ [34] , [35] , [36] , [37] ]. The EMT triggered by TGF-β1 closely mimics a crucial pathological event in the progression of renal tubulointerstitial fibrosis [ 38 ]. In this work, we constructed the in vitro model of renal tubulointerstitial fibrosis by stimulating human renal proximal tubular epithelial cells HK-2 with TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…These changes consist of a loss of cell adhesion and polarity, while gaining the ability to migrate and invade, as well as the capacity to deposit excessive ECMs. These events have been described in various organs, including the cardiovascular system [ 53 ], kidneys [ 54 ], and lungs [ 55 ], and the intestine [ 56 ]. Additionally, it is noteworthy that besides EMT, mesenchymal-to-epithelial transition (MET) is possible and contributes to wound repair and oncogenesis [ 57 ].…”
Section: The Role Of Immune Dysregulation In Driving Epithelial-to-me...mentioning
confidence: 99%
“…In the literature, there are three types of EMT described: the ones associated with embryogenesis/development (type-1 EMT); the ones involved in wound healing (type-2 EMT); and the ones associated with cancer progression (type-3 EMT) ( Marconi et al, 2021 ). Several studies have reported that damaged epithelial cells may act as crucial sources of fibroblasts and contribute to organ fibrosis through type-2 EMT in different fibrotic tissues ( Tennakoon et al, 2015 ; Rout-Pitt et al, 2018 ; Ortiz-Masiá et al, 2020a ; Macias-Ceja et al, 2022 ; Hadpech and Thongboonkerd, 2023 ) where specialized epithelial cells give rise to myofibroblasts with profibrotic and pro-inflammatory activity, which expresses α smooth muscle actin (α-SMA) and VIMENTIN but does not express epithelial markers, such as E-CADHERIN (CDH1), ZONULAE OCCLUDENTES (ZOS) or claudins. Various transcriptional factors regulate the process, such as SNAIL Family Transcriptional Repressor (SNAIL1/2), ZINC-FINGER E-BOX-BINDING (ZEB1/2), SLUG or TWIST transcription factors (TWIST1/2) ( Xu et al, 2019 ).…”
Section: Emt Role In Intestinal Fibrosismentioning
confidence: 99%